Sustainable approach of high-pressure agave bagasse pretreatment for ethanol production - Aguirre-Fierro, Arelí; Ruiz, Héctor A.; Cerqueira, Miguel A.; Ramos-González, Rodolfo; Rodríguez-Jasso, Rosa M.; Marques, Susana; Lukasik, Rafal M. (Renewable energy, 2020)
Agave bagasse is one of the most abundant lignocellulosic residues readily available for valorization. The agave bagasse was pretreated by applying high-pressure CO2–H2O mixture at temperatures ranging from 150 to 190 °C for a residence time varying from 10 to 50 min. Subsequently, solid phase obtained from pretreatment was subject to enzymatic hydrolysis at high solid loadings. Under optimal conditions, the process integrating pretreatment followed by enzymatic hydrolysis yielded 75.8 mol% of the polysaccharides present in the biomass converted into oligo- or monosaccharides, providing 110.5 g/L of reducing sugars. The monosaccharides present in the obtained hydrolysate were successfully fermented into ethanol, demonstrating the feasibility of performing its biological conversion to commercial biofuels or biochemicals. Thereby, the present study has demonstrated the proof of concept of use of more sustainable high-pressure CO2–H2O pretreatment in the context of lignocellulosic residual biomass valorization based on the biochemical sugar platform. [Display omitted] •Pretreatment of biomass with CO2 was efficient in hemicellulose removal.•Solid from bagasse agave pretreatment was successfully enzymatically hydrolyzed.•XRD and SEM confirmed a positive effect of pretreatment on the enzymatic hydrolysis.•Proof of concept of ethanol production from sugar stream was accomplished.•Pretreatment did not produce inhibitors for ethanolic fermentation.